Les chasseurs d'Aurochs de La Borde Un site du Paléolithique moyen (Livernon, Lot) - Jaubert, Jacques (Documents d'archéologie française, 1990)
This study in paleo-ethnology constantes a decisive contribution to knowledge of lifestyles during the Middle Paleolithic and the relationships of Man with his animal and mineral environments. The La Borde aven is one of the first, if not indeed the first French deposit front this period, for which it has been possible to demonstrate more or less systematic exploitation of a single large herbivore, the Aurochs. In spite of the difficult conditions of an urgent rescue excavation, a multidisciplinary team associating researchers from the Ministère de la Culture, from the CNRS and the Universities carried out a study based on stratigraphic analysis and lithic and faunal remains; these lead the authors from a discussion of the type of site (natural trop, waste site or dwelling-site) to an examination of Paleolithic subsistence strategies (scavenging, hunting or mixed economy) and a definition of territories occupied and tool management concepts.